2006
DOI: 10.1080/10576100600641899
|View full text |Cite
|
Sign up to set email alerts
|

Jihadism in Western Europe After the Invasion of Iraq: Tracing Motivational Influences from the Iraq War on Jihadist Terrorism in Western Europe

Abstract: This article investigates the importance of the invasion and occupation of Iraq as motivation for recent acts of jihadist terrorism in Western Europe. It analyses the mass casualty terrorist attack attributed to a group of Islamist militants in Madrid on 11 March 2004, and the killing of a Dutch filmmaker on the streets of Amsterdam by anAl Qaeda-inspired terrorist network. The first case has been assumed to be mainly motivated by the Iraq war, whereas the other case has been perceived as an act by an individu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0
7

Year Published

2011
2011
2020
2020

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(25 citation statements)
references
References 0 publications
1
17
0
7
Order By: Relevance
“…In addition to protesting military presence in Afghanistan and Iraq (Austria had no officers in Iraq and just four in Afghanistan), domestic Austrian affairs were also attacked, including the introduction of student fees (Musharbash, 2007). Similarly, in a note which Mohammed Bouyeri pinned to van Gogh's body, he expressed outrage at domestic Dutch policy towards Muslims, including proposed 'screening' measures for Muslim immigrants, which were viewed as part of a Jewish conspiracy (Nesser, 2006b).…”
Section: Conditions In the Westmentioning
confidence: 99%
“…In addition to protesting military presence in Afghanistan and Iraq (Austria had no officers in Iraq and just four in Afghanistan), domestic Austrian affairs were also attacked, including the introduction of student fees (Musharbash, 2007). Similarly, in a note which Mohammed Bouyeri pinned to van Gogh's body, he expressed outrage at domestic Dutch policy towards Muslims, including proposed 'screening' measures for Muslim immigrants, which were viewed as part of a Jewish conspiracy (Nesser, 2006b).…”
Section: Conditions In the Westmentioning
confidence: 99%
“…These were characterised by different profiles in terms of political/ideological motivation, organisational affiliation, socio-economic background, education, criminal records, and the use of violence. A study of Jihadi terrorist cells in Europe by Petter Nesser [15,16,17] found that these cells typically consisted of four main categories of terrorist cell members -the entrepreneur, the protégé, the misfit and the drifter. Each type had different socio-economic background and related to ideology and politics in different ways.…”
Section: For Example the Report Of The Official Account Of The Bombimentioning
confidence: 99%
“…Mohammed Bouyeri, van Gogh's murderer, belong to the Hofstad Group, a Dutch jihadist group led by Syrian radical preacher Abu Khatib [75]. The very same group had plans to bomb Amsterdam international airport and government buildings [76].…”
Section: Journal Of Terrorism Research Volume 2 Issuementioning
confidence: 99%